Is hypertension a risk factor for poor balance control in elderly adults? - DEMİRBÜKEN, İLKŞAN (SOC PHYSICAL THERAPY SCIENCE, 2015)
[Purpose] The aim of this study was to investigate whether hypertension negatively affects the postural balance control of elderly adults under different sensory conditions. [Subjects and Methods] Fifty-four healthy elderly adults who were residents in a Geriatric Home Care Center were recruited for this study. Height, weight, body mass index and age of the volunteers were recorded. After applying the exclusion criteria, the final study group included 16 hypertensive (HT) and the control group included 10 non-hypertensive (Non-HT) healthy elderly adults. To evaluate postural balance control objectively, the modified Clinical Test of Sensory Interaction on Balance (modified CTSIB) test was performed under four different conditions: 1) eyes open on a stable surface; 2) eyes closed on a stable surface; 3) eyes open on an unstable surface; and 4) eyes closed on an unstable surface. [Results] The postural balance scores (center of gravity sway) of the HT group were slightly higher than those of the Non-HT group under conditions 1 (HT group=0.3 degrees/sec, Non-HT group=0.2 degrees/sec), 2 (HT group=0.8 degrees/sec, Non-HT group=0.4 degrees/sec) and 4 (HT group=4.5 degrees/sec, Non-HT group=3.5 degrees/sec), but no statistically significant differences were found between the HT and Non-HT groups under any sensory condition. [Conclusion] The result of this study indicate that controlled hypertension in elderly adults is not a cause of worse balance performance than controls on stable or unstable surfaces with the eyes open or closed.
Keywords: Hypertension; Postural balance; Posture; QUALITY-OF-LIFE; COMPUTERIZED POSTUROGRAPHY; INTRACRANIAL HYPERTENSION; OLDER-ADULTS; HYPOTENSION; MECHANISM; AGE